Mammal occurrence and roadkill in two adjacent ecoregions (Atlantic Forest and Cerrado) in south-western Brazil - Cáceres, Nilton C. (2010)
This paper examines the frequencies of mammal roadkill in two adjacent biogeographic ecoregions (Atlantic Forest and Cerrado) of Brazil. Mammals were recorded during a seven-year period and over 3,900 km of roads, in order to obtain data for frequencies of species in habitats (sites) and frequencies of species killed by cars on roads. Sites (n = 80) within ecoregions (Cerrado, n = 57; Atlantic Forest, n = 23) were searched for records of mammals. Species surveyed in the entire region totaled 33, belonging to nine orders and 16 families. In the Cerrado, 31 species were recorded in habitats; of these, 25 were found dead on roads. In the Atlantic Forest ecoregions, however, we found 21 species in habitats, 16 of which were also found dead on roads. There was no overall significant difference between ecoregions for frequencies of occurrence in habitats or for roadkills, but there were differences between individual species. Hence, anteaters were mostly recorded in the Cerrado ecoregion, whereas caviomorph rodents tended to be more frequent in the Atlantic Forest ecoregion (seen mainly by roadkills). The greater number of species (overall and threatened) and the greater abundance of species records in the Cerrado suggest that this ecoregion has a greater biodiversity and is better conserved than the Atlantic Forest ecoregion, in the state of Mato Grosso do Sul, south-western Brazil.